Population genetics of venous thromboembolism - Margaglione, Maurizio; Grandone, Elvira (Thrombosis and Haemostasis, 2011)
Results from epidemological studies are consistent with the hypothesis that disparities in venous thromboembolism (VTE) burden are attributable to differences in genetic structure among populations from different genetic backgrounds. To that end, recent genetic studies have demonstrated not only potential associations between certain alleles and VTE but also clear differences in the distribution of these alleles in patients stratified by ancestry. There are a number of notable clinical and pathophysiological questions that arise from these findings. First at all is defining the precise variant(s) that alter disease susceptibility. The comparatively lower rates of VTE recorded among Asians would imply that risk profile is devoid of many risk factors on comparison to Caucasian or African counterparts or that a putative protective factor is advocated in the former population. Identification of these variants provided specific insight into VTE disease in selected populations and also shed lights on the biology of the disease. The association observed between ancestry and VTE is likely to be multifactorial, possibly reflecting, in addition to genetic variation, also socioeconomic differences. Acknowledgment of this may provide useful information in biomedical contexts and help to identify individual risk factors for VTE.
Keywords: Epidemiological studies; familial thrombosis; gene mutations; thrombophilia; inherited coagulation disorders